Preparation method of mixed positive electrode material, positive electrode plate and sodium ion battery
By mixing NA2FE2 (SO4) 3 with O3-NA [NI1/3FE1/3MN1/3] O2 or O3-NA [NI1/2MN1/2] O2, prepare high energy density and higher security positive pole films. Solved the problem of low -capacity and conductivity of NA2FE2 (SO4) 3 in sodium ion batteries, and realized the extension of the battery life and the improvement of safety performance.
Patent Information
- Application Number
- CN202411582901.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-07
- Publication Date
- 2025-01-28
AI Technical Summary
The application of Na2Fe2(SO4)3 in sodium ion batteries has problems such as low reversible specific capacity, poor material conductivity, high charging voltage platform and high overall impedance of the electrode sheet, resulting in low cell life and insufficient safety.
By mixing Naxfey (S04) Z and O3-NA [NI1/3FE1/3MN1/3] O2 or O3-NA [ni1/2mn1/2] O2, prepare a mixed positive material, and through the transferor coating machine It is evenly applied to the aluminum foil collection of fluids to form a high -energy density and higher security.
This method not only improves the energy density and safety performance of the battery cell, but also reduces the charging voltage platform, reduces the risk of dissolving gas and cathode transition metals, and extend the life of the battery cell.
Smart Images

Figure CN119381434A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of sodium ion technology, and in particular to a method for preparing a mixed positive electrode material, a positive electrode sheet and a sodium ion battery. Background Art
[0002] As a supplement to lithium-ion batteries, sodium-ion batteries are expected to be used in low-speed electric vehicles, communication base stations, large-scale energy storage and other fields. Compared with lithium-ion batteries, the advantage of sodium-ion batteries is that the crustal reserves of sodium resources are abundant (2.75%), which is more than 400 times that of lithium (0.0065%), and the global distribution is uniform and the extraction is simple. In addition, the internal resistance of sodium-ion batteries is higher than that of lithium-ion batteries, the instantaneous heat generation is less in the case of short circuit, the temperature rise is lower, the thermal runaway temperature is higher than that of lithium batteries, and they have higher safety; the operating temperature range of sodium-ion batteries is wider (-40℃ to 80℃), which is suitable for extremely cold and hot scenes; sodium-ion batteries have excellent fast charging capabilities, and the charging time only takes about 10 minutes; sodium-ion batteries can use aluminum foil as positive and negative current collectors, and the current collector cost is lower. Therefore, it is of great significance to develop high-efficiency and low-cost sodium-ion battery technology. Na2Fe2(SO4)3, as a sulfate polyanion material, has strong electronegativity and redox potential, and is a sodium storage material with great potential. Although the energy density of sulfate polyanion materials is low, the cost of raw materials is controllable. According to the current market price, under ideal circumstances, the theoretical raw material cost of Na2Fe2(SO4)3 is only 500.4 yuan / ton (theoretical calculation based on the molecular formula, ignoring losses, excluding processing costs, etc.), which has a significant advantage in theoretical raw material cost over lithium battery positive electrode materials and other sodium battery positive electrode materials.
[0003] However, in the practical application process of Na2Fe2(SO4)3 in the prior art, the main disadvantages are as follows: 1. The reversible specific capacity of Na2Fe2(SO4)3 in the voltage range of 2-4.5V is only 90mAh / g at most, while the minimum gram capacity of other layered oxides and Prussian blue positive electrode main materials is ≥100mAh / g. And because the intrinsic conductivity of the material is poor, the existing technical modification focuses on increasing the conductivity of the material - introducing C, N / P or other metal elements, which is bound to cause a loss in the material's gram capacity; 2. The voltage platform used by Na2Fe2(SO4)3 is ≥3.5V. The higher platform voltage produces an extremely high oxidation reaction potential, which increases gas production and deteriorates the calendar life of the battery cell. In addition, high voltage is an intrinsic reaction and is difficult to change with existing modifications; 3. The intrinsic conductivity of the Na2Fe2(SO4)3 electrode is poor, and its structure is lamellar, the electrical contact of the active material is poor, and the traditional coating introduces SP (conductive carbon black) and CNT (carbon nanotubes) to form a two-level conductive network. Due to the lamellar structure, the adhesion area of the conductive additive is limited, resulting in a high overall impedance of the electrode. High electrode impedance leads to large overall polarization of the cell and a short cell life. Summary of the invention
[0004] In order to solve the above technical problems, the present invention provides a method for preparing a mixed positive electrode material, a positive electrode plate and a sodium ion battery, which can reduce the charging voltage platform, increase the discharge voltage platform, reduce the cathode potential during the charging process, reduce the risk of gas production and cathode transition metal dissolution, improve safety and life, and increase the overall energy density of the battery cell.
[0005] The technical solution provided by the present invention is as follows: A method for preparing a mixed positive electrode material comprises the following steps: S1, Na x Fe y (S04) z Passing through a sieve with a pore size of 4 to 6 μm, collecting the undersize as the first material, where 1≤x≤3, 1≤y≤2, 2≤z≤4; S2. Put O3-Na[Ni 1 / 3 Fe 1 / 3 Mn 1 / 3 ]O2 or O3-Na[Ni 1 / 2 Mn 1 / 2 ]O2 passes through a sieve with a pore size of 4 to 6 μm, and the material under the sieve is collected as the second material; S3, mixing the first material and the second material in a certain ratio to prepare a mixed positive electrode active material; S4. Add a binder, conductive carbon black and carbon nanotubes to the mixed positive electrode active material in a certain proportion and mix them evenly to obtain a mixed positive electrode material.
[0006] Preferably, in step S3, the first material and the second material are mixed in the following ratio by mass fraction (%): 80-100 parts of the first material and 1-20 parts of the second material.
[0007] Preferably, in step S4, the positive electrode active material is mixed with the binder, conductive carbon black and carbon nanotubes in the following ratio by mass fraction (%): 92-98 parts of the mixed positive electrode active material, 0.5-2 parts of the conductive carbon black, 1-4 parts of the binder, and 0.3-1 part of the carbon nanotubes.
[0008] Preferably, the adhesive used in step S4 is one or a combination of polyvinylidene fluoride and N-methylpyrrolidone.
[0009] A positive electrode plate comprises the mixed positive electrode material prepared by the above-mentioned method for preparing the mixed positive electrode material.
[0010] Preferably, the mixed positive electrode material is first adjusted to a viscosity of 3000-5000 mPa.s by N-methylpyrrolidone to obtain a slurry, and then the slurry is evenly coated on an aluminum foil current collector by a transfer coater to obtain a positive electrode sheet.
[0011] Preferably, during the coating process, the coating surface density is controlled to be between 150 and 450 μg / 1540.25 cm by adjusting the height of the transfer coater blade. 2 , the coating speed is set to 3-5 m / min, and the oven temperature is set to 70-110°C.
[0012] Preferably, the prepared positive electrode plate is cold pressed, the cold pressing pressure is 20-40T, the compaction is 1.6-2.0, the cold pressed plate is wound into a core, and then assembled into a 26700 cylindrical battery cell for electrochemical performance testing.
[0013] Preferably, the prepared positive electrode sheet is punched into discs with a diameter of 15 to 25 mm, and the negative electrode sheet, the separator, and the positive electrode sheet are assembled into button cells in this order for testing the gram capacity of the material.
[0014] A sodium ion battery comprises the mixed positive electrode material prepared by the method for preparing the mixed positive electrode material described above or comprises the positive electrode sheet described above.
[0015] The present invention has the following advantages over the prior art: 1. The present invention introduces a small amount of O3 material to obtain a huge energy density improvement in a simple way, breaking through the maximum gram capacity of sodium iron sulfate in sodium ion batteries; 2. The present invention simultaneously utilizes two materials with different particle size ratios to improve the compaction of the positive-stage sheet of the system, and the small-particle-size, high-conductivity O3 material is simultaneously involved in the construction of the second conductive network, solving the problem that the sodium iron sulfate sheet has poor overall conductivity due to the poor intrinsic conductivity of the sodium iron sulfate material; 3. The present invention utilizes the low voltage platform of O3 material and the charging curve is similar to the characteristics of sodium ferric sulfate, which reduces the charging voltage platform of sodium ferric sulfate sodium ion battery, increases the discharge voltage platform, reduces the risk of gas production and sodium precipitation during the charging process, increases the discharge capacity density, and further improves the safety performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments recorded in the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0017] Figure 1 This is a charge and discharge curve diagram of an embodiment of the present invention in which a small amount of O3 material is introduced. DETAILED DESCRIPTION
[0018] In order to enable those skilled in the art to better understand the technical solutions in the present invention, the technical solutions in the embodiments of the present invention are clearly and completely described below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in the field without creative work are within the scope of protection of the present invention.
[0019] Embodiment 1: A method for preparing a mixed positive electrode material comprises the following steps: S1, Na x Fe y (S04) z Passing through a sieve with a pore size of 4 to 6 μm, collecting the undersize as the first material, where 1≤x≤3, 1≤y≤2, 2≤z≤4; S2. Put O3-Na[Ni 1 / 3 Fe 1 / 3 Mn 1 / 3 ]O2 passes through a sieve with a pore size of 4 to 6 μm, and the material under the sieve is collected as the second material; S3, mixing the first material and the second material in a certain ratio to prepare a mixed positive electrode active material; S4. Add a binder, conductive carbon black and carbon nanotubes to the mixed positive electrode active material in a certain proportion and mix them evenly to obtain a mixed positive electrode material.
[0020] In this embodiment, in step S3, the first material and the second material are mixed in the following ratio by mass fraction (%): 80-100 parts of the first material and 1-20 parts of the second material.
[0021] In this embodiment, in step S4, the positive electrode active material is mixed with the binder, conductive carbon black and carbon nanotubes in the following ratio by mass fraction (%): 92-98 parts of the mixed positive electrode active material, 0.5-2 parts of the conductive carbon black, 1-4 parts of the binder, and 0.3-1 parts of the carbon nanotubes.
[0022] In this embodiment, the adhesive used in step S4 is one or a combination of polyvinylidene fluoride and N-methylpyrrolidone.
[0023] A positive electrode plate comprises the mixed positive electrode material prepared by the above-mentioned method for preparing the mixed positive electrode material.
[0024] In this embodiment, the mixed positive electrode material is first adjusted to 3000-5000mpa.s by N-methylpyrrolidone to obtain a slurry, and then the slurry is evenly coated on the aluminum foil current collector by a transfer coater to obtain a positive electrode plate. The specific process of making the mixed positive electrode material is as follows: the mixture of polyvinylidene fluoride and N-methylpyrrolidone is stirred at 25 / 3000rpm for 4h to obtain a binder slurry, and then the mixed positive electrode active material, SP (conductive carbon black) and CNT (carbon nanotube) are added respectively, and the stirring tank speed is maintained at 25 / 3000rpm to fully mix the main and auxiliary materials. The stirring time is expected to be 4h, and finally the viscosity needs to be adjusted to 3000-5000mpa.s by NMP, and the slurry state without gel and sedimentation is the shipping slurry state.
[0025] In this embodiment, during the coating process, the coating surface density is controlled to be between 150 and 450 μg / 1540.25 cm by adjusting the height of the transfer coater blade. 2 , the coating speed is set to 3-5 m / min, and the oven temperature is set to 70-110°C.
[0026] In this embodiment, the prepared positive electrode plate is cold pressed, the cold pressing pressure is 20-40T, and the compaction is 1.6-2.0. The cold pressed plate is wound into a core and assembled into a 26700 cylindrical battery cell for electrochemical performance testing.
[0027] In this embodiment, the prepared positive electrode plate is punched into discs with a diameter of 15 to 25 mm, the negative electrode uses a sodium plate of the same size, the electrolyte uses the Na2Fe2(SO4)3 special electrolyte sold by Wanfu Company, the diaphragm uses Celgard 12μm PP diaphragm, and the negative electrode plate, the isolation membrane, and the positive electrode plate are assembled in order into a button battery for testing the gram capacity of the material.
[0028] After actual testing, the test results are as follows Table 1 and Figure 1 As shown in Table 1, it can be seen that with only 3% mixing amount, the gram capacity is increased by 13% compared with pure Na2Fe2(SO4)3; and the voltage platform of O3 material is lower than that of NFS. After mixing, the charging voltage platform can be reduced and the discharge voltage platform can be increased. The charging voltage platform is reduced, and at the same time, the cathode potential can be reduced during charging, reducing the risk of gas production and cathode transition metal dissolution, and improving safety and life; the voltage platform rises during the discharge process, because energy = platform voltage * capacity, the platform voltage rises, and the overall energy density of the battery cell is increased. Figure 1It can be seen that the introduction of a very small amount of O3 material greatly reduces the end slope of the discharge curve, increases the 3.0-2.0V discharge capacity, and reduces the discharge voltage platform to a certain extent; the charging platform is also reduced by about 0.3V due to the introduction of O3 material, the sodium ion embedding in the charging process is smoother, the CV time is shortened, the charging polarization is reduced, the risk of sodium precipitation in the charging process is reduced, and the safety and rate performance are improved.
[0029] A sodium ion battery comprises the mixed positive electrode material prepared by the method for preparing the mixed positive electrode material or comprises the positive electrode plate.
[0030] Table 1 Material gram capacity test results
[0031] Embodiment 2: The difference between this embodiment and embodiment 1 is that the second material is graded to a pore size of 1-2 μm through a sieve, and then the first material and the second material are mixed according to the proportion in Table 1 and used as the main material for homogenization. The remaining steps are the same as in embodiment 1. Since the homemade Na2Fe2(SO4)3 is a lamellar structure material, the contact points between particles are small, resulting in high electrode resistance and low compaction. By filling the NFS gap with O3 material with a smaller particle size and better conductivity, a better primary conductive network can be constructed, the electrode resistance can be reduced, the polarization can be reduced, and the system life can be improved; and the large particle gaps are filled with O3, which increases the system compaction to a certain extent and increases the energy density.
[0032] Embodiment 3: The difference between this embodiment and the first embodiment is that the second material type O3-Na[Ni 1 / 3 Fe 1 / 3 Mn 1 / 3 ]O2 is replaced by O3-Na[Ni 1 / 2 Mn 1 / 2 ]O2, remove the Fe element in the system, and increase the proportion of Ni and Mn. At present, the mainstream understanding of the cyclic failure of the sodium iron sulfate system is that the Fe element will occupy the embedding site of the Na element, forming a Fe / Na mixed arrangement, resulting in irreversible capacity loss. At the same time, at the high potential of the positive electrode, that is, the full battery over-discharge state, the Fe element is at risk of dissolution. Excess Fe elements are dissolved. Due to their strong polarity, the charging process will preferentially reduce them at the negative electrode, react with the electrolyte to produce hydrogen, and attack the anode SEI at the same time. Therefore, the Fe element in the O3 material is removed, and more Mn elements are introduced. Mn itself exists as a stable structure in the crystal phase of the material, and can also be used as a priority reaction element to reduce the risk of Fe element dissolution in sodium iron sulfate. The polarity of the Mn element itself is higher than that of the Fe element, which can also prevent the dissolved Fe element from reacting with the electrolyte and the anode SEI film, thereby achieving the technical effect of improving the life and safety performance of the system.
[0033] The above description of the disclosed embodiments enables those skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features disclosed herein.
Claims
1. A method for preparing a mixed positive electrode material, characterized in that: The steps are as follows: S1, Na x Fe y (S04) z Passing through a sieve with a pore size of 4 to 6 μm, collecting the undersize as the first material, where 1≤x≤3, 1≤y≤2, 2≤z≤4; S2. Put O3-Na[Ni 1 / 3 Fe 1 / 3 Mn 1 / 3 ]O2 or O3-Na[Ni 1 / 2 Mn 1 / 2 ]O2 passes through a sieve with a pore size of 4 to 6 μm, and the material under the sieve is collected as the second material; S3, mixing the first material and the second material in a certain ratio to prepare a mixed positive electrode active material; S4. Add a binder, conductive carbon black and carbon nanotubes to the mixed positive electrode active material in a certain proportion and mix them evenly to obtain a mixed positive electrode material.
2. The method for preparing a mixed positive electrode material according to claim 1, characterized in that: In the step S3, the first material and the second material are mixed in the following proportions by mass fraction (%): 80-100 parts of the first material and 1-20 parts of the second material.
3. The method for preparing a mixed positive electrode material according to claim 1, characterized in that: In step S4, the positive electrode active material is mixed with a binder, conductive carbon black and carbon nanotubes in the following proportions by mass fraction (%): 92-98 parts of the mixed positive electrode active material, 0.5-2 parts of the conductive carbon black, 1-4 parts of the binder and 0.3-1 parts of the carbon nanotubes.
4. The method for preparing a mixed positive electrode material according to claim 1, characterized in that: The adhesive used in step S4 is one or a combination of polyvinylidene fluoride and N-methylpyrrolidone.
5. A positive electrode sheet, characterized in that: A mixed positive electrode material prepared by the method for preparing a mixed positive electrode material according to any one of claims 1 to 4.
6. The positive electrode sheet according to claim 5, characterized in that: The mixed positive electrode material is first adjusted to a viscosity of 3000-5000 mpa.s by N-methyl pyrrolidone to obtain a slurry, and then the slurry is evenly coated on an aluminum foil current collector by a transfer coater to obtain a positive electrode sheet.
7. The positive electrode sheet according to claim 6, characterized in that: During the coating process, the coating surface density is controlled to be between 150 and 450 μg / 1540.25 cm by adjusting the height of the transfer coater blade. 2 , the coating speed is set to 3-5 m / min, and the oven temperature is set to 70-110°C.
8. A sodium ion battery, characterized in that: A mixed positive electrode material prepared by the method for preparing a mixed positive electrode material according to any one of claims 1 to 4 or a positive electrode sheet according to any one of claims 5 to 7.